Providing home care for older adults : a professional guide for mental health providers - Terry, Danielle L.; Mlinac, Michelle E.; Steadman-Wood, Pamela L. (New York, NY : Routledge, 2021)
"A practical guide to providing home-based mental health services, Providing Home Care for Older Adults teaches readers to how to handle the unique aspects of home-based care and apply and adapt evidence-based assessment and treatment within the home-based setting. Featuring contributions from experienced, board-certified home care psychologists, social workers, and psychiatrists, the book explains the multifaceted role of a home-based provider, offers concrete and practical considerations for working within the home, and highlights adaptations to specific evidence-based methods used within the home. Also covered are special topics related to hoarding, safety, capacity evaluations, caregivers, case management, and use of technology. Each chapter includes engaging case examples with practical tips that illustrate what it is like to work in this new and exciting frontier. Psychologists, counselors, and other mental health practitioners in home settings will be able to use this guide to provide effective home-based care to older adults"--
OCLC-licensed vendor bibliographic record.
Keywords: Home care services; Mental health services; Mental illness; MEDICAL / Nursing / Home & Community Care; MEDICAL / Nursing Home Care; PSYCHOLOGY / Mental Health